Respon Pertumbuhan Anggrek Dendrobium sp. Terhadap Konsentrasi BAP (Benzyl Amino Purine) Pada Media Cair Dan Padat Secara In Vitro - Luthfi Nur Aprillia Santoso (Fakultas Pertanian, 2026)
Dendrobium sp. orchid is an ornamental plant with a wide variety of flowers and high commercial value. However, its production remains limited compared to market demand. Therefore, in vitro propagation techniques are needed to increase production and shorten the cultivation time. The selection of explants and media composition are critical factors in the success of tissue culture. This study aimed to determine the appropriate BAP concentration and culture media form for the in vitro growth of Dendrobium sp. PLB. This study used a factorial Completely Randomized Design (CRD) with two factors. The first factor was BAP concentration, consisting of 3 levels: B1 = 1 ppm; B2 = 1,5 ppm; B3 = 2 ppm. The second factor was the culture media form, consisting of two levels: M1 = liquid medium dan M2 = solid medium. All treatments were replicated 4 times, and each treatment consisted of 10 explants. Data were analyzed using Analysis of Variance (ANOVA) test at a 5% significance level. The results showed that there was no interaction between BAP concentration and media form on all observed variables. The BAP concentration factor treatment had No. effect on all observed variables. The media factor treatment affected the number of shoots, number of leaves, root length, leaf area, height growth rate, and leaf color at R value, with the best treatment being solid medium.
Validasi dan Finalisasi Repositori File 02 Juli 2026_Kholif Basri
Keywords: Dendrobium sp.; In vitro; BAP; Culture medium